Developing Competences and Civic Attitudes among Territorial Defence Personnel - Wojciech Horyń; Lesław Wełyczko (Edukacja Ustawiczna Dorosłych)
: This article presents aspects of competence preparation of Territorial Defence Force (TDF) soldiers to perform tasks in accordance with their intent – albeit due to the vastness of the subject matter it only partially explores this topic. Additionally, this article indicates rather important aspects of forming soldiers’ personalities and in consequence also their attitudes (civic, patriotic, national defence-oriented etc.) which combine to form their professionalpersonal characteristics. Currently, Territorial Defence Force is in the centre of attention of all those who are responsible for implementation and finalization of the forming process of this new type of Armed Forces of the Republic of Poland. Therefore, all aspects that are responsible for improvement of the process become important